Interaction of cyclic and linear labaditin peptides with anionic and zwitterionic micelles - Barbosa, S.C.; Cilli, Eduardo Maffud [UNESP]; Dias, Luis Gustavo; Fuzo, Carlos Alessandro; Degrève, Léo; Stabeli, Rodrigo G.; Itri, Rosângela; Ciancaglini, P. (Elsevier, 2014)
Conformational changes of the cyclic (Lo) peptide Labaditin (VWTVWGTIAG) and its linear analogue (L1) promoted by presence of anionic sodium dodecyl sulfate (SDS) and zwitterionic L-α-Lysophosphatidylcholine (LPC) micelles were investigated. Results from λmax blue-shift of tryptophan fluorescence emission combined with Stern–Volmer constants values and molecular dynamics (MD) simulations indicated that L1 interacts with SDS micelles to a higher extent than does Lo. Further, the MD simulation demonstrated that both Lo and L1 interact similarly with LPC micelles, being preferentially located at the micelle/water interface. The peptide–micelle interaction elicits conformational changes in the peptides. Lo undergoes limited modifications and presents unordered structure in both LPC and SDS micelles. On the other hand, L1 displays a random-coil structure in aqueous medium, pH 7.0, and it acquires a β-structure upon interaction with SDS and LPC, albeit with structural differences in each medium.
Keywords: Labaditin; Cyclic peptide; Circular dichroism; Fluorescence; Molecular dynamic